علم الناسخ والمنسوخ کا قرآنی تصور: ایک تحقیقی جائزہ: The Qur’anic concept of Al-Nāsikh wal-Mansūkh:A research review - Saad Jaffar; Dr. Muhammad Ayaz (International Research Journal of Arabic and Islamic Studies, 2022)
Islam is a perfect religion which has no precedent in the religions of current universe. The base of this religion is the Qur'an and the Qur'an is the word of the Almighty Allah which the Almighty Himself has taken the responsibility of protecting. This word is a collection of characteristics prevalent in the world. Filled with all the features of this mortal world, this word is full of wisdom. One of these wisdoms is Nasikh and Mansokh. It is also important to know that not all the rules of the Qur'an were revealed at once, but the facilitation of the implementation of the rules has been kept in mind. The reason for this is that, it is easier and more permanent to follow the rules that have been enacted slowly and with respite. The concept of Nasikh and Mansokh has been one of the most important concepts in the Qur'an, on which the scholars of the Ummah have written extensively in every age. From which the importance of this subject can be gauged on what is the importance of this subject among the scholars of the ummah. The present research work will explain the methodology of the classical and neo classical scholars about Nasikh and Mansokh and also explained the thoughts of Orientalists, which distorted the Qur'anic philosophy of Nasikh and Mansokh. It will also explain the perception of Orientalists which is flawed. The Nasakh (concept) is not only a feature of the Holy Quran but it is also proved in the Shariha of the previous Prophets. If the opinions of the leading neo-classical scholars regarding Nasakh are taken into account, then it is as, if it is very meager.